(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
This article aims to reconstruct the Italian system of deputising and succession of office holders in the case of death or impediment, looking for any criticalities related to the possibility of multiple vacancies during the epidemic. Most important positions at national, regional and local level are analised. Further, short notes are devoted to collegiate bodies, such as the Constitutional Court and the Council of Ministers.